Alienation and Women's Experience in Contemporary Fiction - Gordić Petković, Vladislava S. (Collection of Papers of the Faculty of Philosophy in Priština, 2018)
The paper is an attempt at illustrating either radical or subtle changes in the ways gender and literature interact when analyzing alienation as one of the most enduring processes and practices operating within the realm of literary topics. The fiction by various women writers ranging from Vida Ognjenović, Danica Vukićević, Nina Živančević and Ljubica Arsić, to prolific contemporary American authors such as Ann Beattie accentuates the identification of women's social self as consistent in presenting communication rituals which enforce alienation. These and many other literary works insist on introducing different kinds of women’s narratives, ranging from intimate confession in letters and journals to experimental practices involving different points of view and focalisation, most often employing a prose style consisting of plain but suggestive words and simple but artfully structured syntax.
Keywords: postmodernism; alienation; literature; women's experience